Engineering the Electrical and Optical Properties of WS2 Monolayers via Defect Control - Michele Giovanni Bianchi; Francesca Risplendi; Michele Re Fiorentin; Giancarlo Cicero (Advanced Science, 2024)
Abstract Two‐dimensional (2D) materials as tungsten disulphide (WS2) are rising as the ideal platform for the next generation of nanoscale devices due to the excellent electric‐transport and optical properties. However, the presence of defects in the as grown samples represents one of the main limiting factors for commercial applications. At the same time, WS2 properties are frequently tailored by introducing impurities at specific sites. Aim of this review paper is to present a complete description and discussion of the effects of both intentional and unintentional defects in WS2, by an in depth analysis of the recent experimental and theoretical investigations reported in the literature. First, the most frequent intrinsic defects in WS2 are presented and their effects in the readily synthetized material are discussed. Possible solutions to remove and heal unintentional defects are also analyzed. Following, different doping schemes are reported, including the traditional substitution approach and innovative techniques based on the surface charge transfer with adsorbed atoms or molecules. The plethora of WS2 monolayer modifications presented in this review and the systematic analysis of the corresponding optical and electronic properties, represent strategic degrees of freedom the researchers may exploit to tailor WS2 optical and electronic properties for specific device applications.